Legal Assistance for Micro, Small, and Medium Enterprises (MSMEs) in Drafting Fair Digital Contracts in the Digital Economy Era - Henny Saida Flora; Wulandari Wulandari; Grenaldo Ginting; Anastasia Sarjono; Suryani Intan Pratiwi Puwa (PT Inovasi Pratama Internasional, 2026)
The rapid expansion of Indonesia’s digital economy has compelled micro, small, and medium enterprises (MSMEs) to enter digital contracts—often standardized agreements imposed by platforms or larger counterparties. These contracts frequently contain unfair terms that disadvantage MSMEs due to their limited legal literacy and bargaining power. This study examines a legal assistance program that aimed to empower MSMEs in Yogyakarta to draft and negotiate fairer digital contracts. Employing a qualitative case study design, data were gathered through in‑depth interviews with 30 MSME owners and five legal assistants, focus group discussions, and comparative document analysis of 60 digital contracts (pre‑ and post‑assistance). Thematic analysis revealed that before assistance, contracts were dominated by clauses unilaterally limiting liability, granting vendors unfettered amendment rights, and imposing burdensome dispute resolution mechanisms. Through a structured mentoring process—comprising legal literacy workshops, clause‑by‑clause review, collaborative redrafting, and negotiation simulations—MSMEs shifted from passive acceptance to active negotiation. Post‑assistance contracts demonstrated significant improvements in fairness indicators such as clarity, balance of obligations, and accessibility of remedies. The study also identified persistent challenges, including the reluctance of dominant platforms to alter standard terms and the need for sustained legal support. The findings underscore the transformative potential of community‑based legal assistance in fostering contractual justice within the digital economy. Policy recommendations include the development of government‑endorsed fair‑contract templates, integration of legal design principles into e‑commerce platforms, and institutionalization of accessible legal aid for MSMEs.